Special Issue: Algorithms in Bioinformatics - Boucher, Christina (Algorithms, 2023)
In the past decade, there has been an effort to sequence and compare a large number of individual genomes of a given species, resulting in a large number of (reference) genomes of various species being made publicly available [...]